2002
DOI: 10.2737/pnw-gtr-530
|View full text |Cite
|
Sign up to set email alerts
|

The status of whitebark pine along the Pacific Crest National Scenic Trail on the Umpqua National Forest.

Abstract: Because of concern over widespread population declines, the distribution, stand conditions, and health of whitebark pine (Pinus albicaulis Englem.) were evaluated along the Pacific Crest National Scenic Trail on the Umpqua National Forest. Whitebark pine occurred on 76 percent of the survey transects. In general, whitebark pine was found in stands with lower overall densities and fewer late-seral species, particularly Shasta red fir (Abies magnifica var. shatensis A. Murr.) and mountain hemlock (Tsuga mertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…Overall, approximately 26% the recently killed limber pine in this study were infected by WPBR. Other studies in more northern and western North American areas have found higher total levels of mortality, including approximately 20% of whitebark pine in British Columbia with from 50% to less than 5% associated with WPBR (Campbell and Antos 2000;Zeglen 2002), 10% of whitebark pine in Oregon (Goheen et al 2002), and 8.7% of limber and whitebark pines in the Intermountain West (Smith and Hoffman 2000). Our lower level of mortality (5%) is most likely a reflection of the shorter time of exposure to rust in our study areas.…”
Section: Discussionmentioning
confidence: 92%
“…Overall, approximately 26% the recently killed limber pine in this study were infected by WPBR. Other studies in more northern and western North American areas have found higher total levels of mortality, including approximately 20% of whitebark pine in British Columbia with from 50% to less than 5% associated with WPBR (Campbell and Antos 2000;Zeglen 2002), 10% of whitebark pine in Oregon (Goheen et al 2002), and 8.7% of limber and whitebark pines in the Intermountain West (Smith and Hoffman 2000). Our lower level of mortality (5%) is most likely a reflection of the shorter time of exposure to rust in our study areas.…”
Section: Discussionmentioning
confidence: 92%
“…6. Whereas significant mortality in high-elevation whitebark pine forests has resulted from non-native white pine blister rust, increasingly mountain pine beetle related mortality is also being observed Powell 2001, 2005;Goheen et al 2002;Waring and Six 2005). (A) Live tree response to water year precipitation and minimum temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Conditions at high elevations generally have been less conducive to extensive insect and disease outbreaks than at lower elevations. Aside from blister rust, which has not been observed as a significant problem in the eastern Sierra Nevada, observations of scattered mortality related to mountain pine beetle (Dendroctonus ponderosae Hopkins) are being reported in other subalpine forests of the West, although these generally have been in stands below 2500 m Powell 2001, 2005;Goheen et al 2002;Waring and Six 2005). The most extensive dieback in subalpine forests of western North America in recent decades is occurring as a result of non-native white pine blister rust (Kendall and Arno 1990).…”
Section: Introductionmentioning
confidence: 99%
“…(2004) observed that plot‐level incidence in northern Idaho ranged from 50 to 96% for mature whitebark pine and 32 to 92% for immature whitebark pine. In a 1998 survey along Oregon’s Cascade Crest, G oheen et al. (2002) observed that about half of the white pine were infected.…”
Section: White Pine Blister Rust Extent and Severity Since 1960mentioning
confidence: 99%
“…Kegley et al (2004) observed that plot-level incidence in northern Idaho ranged from 50 to 96% for mature whitebark pine and 32 to 92% for immature whitebark pine. In a 1998 survey along OregonÕs Cascade Crest, Goheen et al (2002) observed that about half of the white pine were infected. In the Blue Mountains of northeastern Oregon, Erickson et al (2007) examined three, isolated, highelevation populations of whitebark pine (4000 trees sampled); blister rust incidence was 27, 64 and 73%, respectively.…”
Section: Whitebark Pinementioning
confidence: 99%